SOME PRELIMINARY OBSERVATIONS ON THE RASTRELLIGER FAUGHNI MATSUI OCCURRING IN THE MADRAS COASTAL WATERS - Gnanamuthu, J C; Girijavallabhan, K G (Indian Journal of Fisheries, 2011)
A preliminary account on the biological observations on the Rastrelligerfaughni Matsui occurring along the Madras coast is given. Unlike the Indianmackerel Rastrelliger kanagurta this species seems to appear in loose concenrations.The species contributes, though in a very minor way, to the fisheries duringFebruary-March, when adults above 220 mm in total length are mainly caught.Juveniles measuring 35-159 mm form a notable portion of whatever mackerel contributionto the shore seine fishery in March and April.